Cefepime Efficacy and Safety in Children: A Systematic Review and Meta-analysis - Jan, Saber; Ragunanthan, Braveen; DiBrito, Sandra R.; Alabi, Omolabake; Gutierrez, Maria (Frontiers in Pediatrics, 2018)
Background: Cefepime is a fourth-generation cephalosporin antibiotic used to treat a variety of infections. The US Food and Drug Administration (FDA) approved its use in certain types of infections among pediatric patients, and yet there have been mixed data about its efficacy and safety in this population. Objective: The objective of this review is to compare efficacy and all-cause mortality of cefepime to other clinically indicated antibiotics among children. Methods: We conducted a systematic search of MEDLINE, EMBASE, CENTRAL, LILACS, and clinicaltrials.gov databases through February 8, 2016. We included randomized controlled trials comparing cefepime to other clinically-indicated antibiotics, placebo or no treatment in children aged 0 to 19 years in the in-patient setting with clinical signs of infection. The primary outcome of interest was all-cause mortality. The secondary outcomes were success rate, treatment failure, and incidence of adverse events. Study quality was assessed using the Cochrane Risk of Bias Assessment Tool. Results: Seventeen studies met the inclusion criteria. There was a total of 1285 participants included, 624 participants in the cefepime arm and 661 in the comparison arm. A random effects meta-analysis for all-cause mortality showed no difference in rates of mortality between cefepime and comparator antibiotics with a mortality risk ratio of 0.88 (95% CI: 0.71 - 1.08). For the secondary outcomes of success rate and treatment failure, a random effects model meta-analysis conducted of the studies showed no difference in rate between cefepime and comparator antibiotics with an overall risk ratio of 0.98 (95% CI: 0.92-1.05) and 1.04 (95% CI: 0.91-1.19), respectively. Adverse events were not statistically assessed given widespread heterogeneity. Overall, the studies had unclear risk of bias, and were limited by high heterogeneity and methodological flaws. Conclusions: The efficacy and safety of cefepime in pediatric patients remain unclear despite the inclusion of newer trials since the last index systematic review conducted a decade ago.